Estimation of potassium concentration in oil palm (Elaeis guineensis Jacq.) leaf tissue by simple and inexpensive water extraction method. (28th July 2016) - Behera, S. K.; Suresh, K.; Rao, B. N.; Manoja, K.; Manorama, K.; Ramachandrudu, K.
ABSTRACT: Estimation of potassium (K) concentration in oil palm leaf tissue is routinely carried out in oil palm plantations to manage fertilizer application for getting higher fresh fruit bunch (FFB) production. Since K in plant tissue is not bound to organic complexes and it is extractable by water, this study was carried out to extract K from oil palm leaf tissue by water extraction method. The results were compared with other established methods like 1 normal (N) ammonium acetate (NH4 OAc) extraction, 0.5 N hydrochloric acid (HCl) extraction, and diacid digestion. The proposed water extraction method consists of shaking of 0.5 g finely ground oil palm leaf tissue with distilled water at 1:60 ratio [sample-to-water weight (w)/volume (v)] for a period of 20 min in a reciprocating shaker, filtration of the content, and measurement of K concentration in filtrate by flame photometer. The results of analysis of 30 oil palm leaf samples collected from various production systems under different soil types and management practices for K concentration revealed the close agreement of water extraction method with other established methods. The mean value of K extracted by water extraction method was within 1–10% of the K extracted by other established methods. Water-extractable K was significantly correlated with K extracted by other methods and it could be predicted by other methods. The values of standard error and coefficient of variation for K extracted by different methods were very low, which indicated that the water extraction method was comparable with other established methods.